Investigation of Flight Performance of Notched Delta Wing Rockets on Different Types of Nose Cones - Özel, Cihan; Macit, Cevher Kürşat; Özel, Meral (My University, 2023)
In this study, four solid fuel model rockets with conical, parabolic, power and haack series nose cones that can carry 4 kg payload at an average altitude of 3 km were designed in the OpenRocket program. Later, the notched delta fin model was mounted on these designed model rockets. The effects of this fin model on the changes in the speed, stability, acceleration, weight and altitude of the rockets were analyzed numerically in the OpenRocket program. As a result of the analysis, it was determined that the conical nose rocket showed the worst flight performance and the Haack series nose cone rocket model showed the best performance. When used with the notched delta fin of the Haack series model, it was determined that the rocket's altitude increased by 7.67%, and its speed increased by 1.83%, but decreased by 1.2% in mach number, 0.6% in weight, 0.3% in acceleration, and 4.5% in stability. As a result, it was seen that it would be beneficial to consider the nose cone and fin together when evaluating the flight performance of the rocket. The results obtained in the study have shown that the notched delta fin model can be used experimentally in defense industry and model rocket applications and the studies can be advanced.
Keywords: OpenRocket program; Nose cones; Notched delta fin; Rocket flight performance